Discrimination of gas diffusion state in intact coal and tectonic coal: Model and experiment. (1st October 2022) - Lu, Shouqing; Li, Mingjie; Sa, Zhanyou; Liu, Jie; Wang, Shengcheng; Qu, Min
Highlights: A general form of simplified diffusion model considering steady-state and unsteady-state diffusion was established. The n in the model, as a gas diffusion state discriminant index, was determined. The gas diffusion state was divided into three zones. Abstract: As the prediction indexes of gas outbursts, the gas content and gas desorption index K1 of drilling cuttings are affected by the gas diffusion in coal particles. According to the current research results, the steady-state and unsteady-state gas diffusion cannot be excellently defined, which leads to the measurement distortion of prediction indexes of gas outbursts in coal particles. Therefore, a general form of simplified diffusion model (GFSDM) considering steady-state and unsteady-state diffusion was established. And the experimental validation and reliability analysis were carried out. The results show that the fitting accuracy of GFSDM for gas diffusion data and the calculation accuracy of the lost gas amount are both greater than those of the simplified unipore diffusion model and simplified mathematical unsteady-state diffusion model. Then, the discriminant index of gas diffusion state and the boundaries of pure diffusion and pure steady diffusion were determined. Based on the boundaries of pure unsteady diffusion and pure steady diffusion, the gas diffusion state was divided into three zones, namely the ultra-negative unsteady diffusion zone, negative unsteady diffusion zone and positive unsteady diffusion zone. The influence mechanism of gas pressure, particle size and tectonism on the gas diffusion state was discussed. It is found that the main reasons for controlling the change of effective diffusion coefficients with time include the influence of diffusion length, influence of free gas pressure and influence of absorbed gas thickness. The research results can improve the gas diffusion theory and provide a theoretical basis for predicting coal and gas outbursts.